Ascending colon cecal junction carcinoma with prostate metastasis: A case report and literature review. Issue 11 (17th March 2023) - Zhu, Wanshan; Wu, Jiaming; Wu, Lexia; Meng, Jincheng; Fang, Cantu; Zhang, Huatang
Abstract : Rationale: Colon carcinoma is the most common type of cancer, and a leading cause of cancer-related death. Clinically, the most common sites of metastases from colon carcinoma are the liver, lungs, peritoneum, and lymph nodes, while the incidence of metastases to the prostate is low. There are few relevant studies on colon carcinoma, most of them being case reports. Patient concerns: A 76-year-old man treated with radical resection of right colon carcinoma due to primary poorly differentiated adenocarcinoma of the cecum. Postoperative pathological examination suggested that he had cancer at the junction of the ascending colon and the cecum. He had received adjuvant chemotherapy after surgery. One year later, he received transurethral plasma resection of the prostate due to urinary system discomfort. Postoperative pathological immunohistochemistry suggested prostate metastasis of colorectal carcinoma, and he received individualized treatment, but this produced no clear survival benefit. Diagnoses: Ascending colon cecal junction carcinoma with prostate metastasis. Interventions: Radical resection, chemotherapy, anti-androgen therapy, surgery to relieve primary lesion obstruction symptoms, and local radiotherapy of the prostate. Outcomes: At present, clinical cases of colon carcinoma with prostate metastasis are rare. By sharing a rare case of ascending colon cecal junction carcinoma with prostate metastasis and reviewing the relevant literature, this paper explores and optimizes the clinical treatment of colon carcinoma with prostate metastasis.